Comparison of Retinal Nerve Fiber Layer Thickness Measurements in Healthy Subjects Using Fourier and Time Domain Optical Coherence Tomography. (29th May 2012) - Pinilla, Isabel; Garcia-Martin, Elena; Idoipe, Miriam; Sancho, Eva; Fuertes, Isabel
Abstract : Purpose . To compare the retinal nerve fiber layer (RNFL) measurements using two different ocular coherence tomography (OCT) devices: Cirrus Fourier domain OCT and Stratus time domain OCT. To analyze reproducibility of Fourier domain measurements in healthy subjects. Methods . One hundred and thirty-two eyes of 132 healthy subjects were scaned on the same day with both instruments, separated by 10 minutes from each other. Thickness of quadrant, average and the 12 different areas around the optic nerve were compared between Cirrus and Stratus. Repeatability, intraclass correlation coefficients (ICCs), and coefficients of variation (COVs) were calculated in RNFL measurements provided by Fourier domain device. Results . The average thickness in the optic cube was 95.50 μ m using Cirrus and 97.85 μ m using Stratus. Average thickness and temporal quadrant showed significant differences using Cirrus and Stratus methods. Reproducibility was better with Fourier domain OCT (mean COV of 4.54%) than with Stratus time-domain OCT (mean COV of 5.57%). Conclusions . Both scan options give reproducible RNFL thickness measurement, but there are differences between them. Measurements obtained using Fourier domain device show better reproducibility.